A Survey of Veterinarian Attitudes Toward Prepubertal Desexing of Dogs and Cats in the Australian Capital Territory - Orr, Bronwyn; Jones, Bidda (Frontiers in Veterinary Science, 2019)
Prepubertal desexing (neutering) has been a legal requirement for all cats and dogs in the Australian Capital Territory since 2001. All cats have to be desexed by 3 months of age, and all dogs are required to be desexed by 6 months of age. The role of veterinary attitudes and behaviors in the implementation of mandatory prepubertal desexing in the Australian Capital Territory is explored in this paper. An online survey was sent to all veterinarians registered in the Australian Capital Territory via the Veterinary Surgeons Board. The survey was designed as a cross-sectional study, hosted using the software REDcap® and analyzed using statistical program R®. A response rate of 14.9% (52/350) of registered veterinarians was achieved. Only 10% of respondents (5/52) recommended that clients have their cat desexed at 3 months of age, the legal maximum age for desexing in the jurisdiction. However, 40% of veterinarians (21/52) thought prepubertal desexing was an appropriate management strategy of cats to prevent overpopulation. Just over one-third of all veterinarians who responded (18/52; 35%) were not aware that prepubertal desexing was mandatory in the Australian Capital Territory. We conclude that prepubertal desexing might be poorly supported by veterinarians in the Australian Capital Territory, even though pets are legally required to undergo prepubertal desexing. As a result, veterinarians may unintentionally be limiting access to this procedure. This has wider policy consequences for Australian and overseas jurisdictions which are considering introducing mandatory prepubertal desexing.